PENGEMBANGAN MODEL PEMBELAJARAN BOTTLE SHOOT PADA PERMAINAN BOLA BESAR UNTUK SISWA KELAS VII DI SMP NEGERI 1 SAMPANG KECAMATAN SAMPANG KABUPATEN CILACAP TAHUN 2016 - Febriani, Saniatun (Journal of Physical Education Health and Sport, 2016)
The purpose of this study is to produce Bottle Shoot game product as learning of futsal big ball game for junior high students that is adapted by capabilities and characteristics. The method of this R&D research is product development research. The obtained datas of Bottle Shoot game product trials are experts’ questionnaire evaluation and students’ questionnaire forms that contain cognitive aspect  and the observations as affective and psychomotor aspect. The final results from physical education and learning experts of the first trial are  81% and 92%. Reinforced by students’ questionnaires results are 83% of psychomotor, 91.7% of affective, and 89.5% of cognitive. The second trial of three schools  an average percentage that is on the cognitive aspects of 91.7%, 87.4% affective, and psychomotor 77.5%. The average of three schools get 85.5%. Based on the percentage of the trial result  can be concluded that Bottle Shoot game can be used as big ball game learning in futsal for junior high school students in Sampang distric, Cilacap.